Protective potential of different compounds and their combinations with MESNA against sulfur mustard-induced cytotoxicity and genotoxicity. (5th June 2017) - Jost, Petr; Fikrova, Petra; Svobodova, Hana; Pejchal, Jaroslav; Stetina, Rudolf
Highlights: The efficacy of 13 molecules was tested against sulfur mustard. The combination of molecules with sodium 2-mercaptoethane sulphonate contributes to enhancing the cytoprotective effect. Sodium thiosulphate and 2-mercaptoethane sulphonate were found to be most effective against sulfur mustard. Abstract: The purpose of this study was to evaluate the efficacy of potential candidate molecules or their combinations against strong alkylation agent sulfur mustard (SM) on the human lung alveolar epithelial cell line A-549. Candidate molecules were chosen on the basis of their previously observed protective effects in vitro . The tested compounds, including antioxidants, sulfhydryl or other sulfur-containing molecules, nitrogen-containing molecules, PARP inhibitors and a NO synthase inhibitor, were applicated 30 min before SM treatment. The efficiency of candidate molecules to protect cells against DNA damage and cell death induced by SM was determined using single-cell gel electrophoresis (comet assay) and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) reduction by viable cells. The damage of DNA was assessed 1 and 24 h after dose 50 μM SM. Cell survival was assessed 24 and 72 h after the exposure. To achieve maximal cytoprotection, combinations of selected compounds with sodium 2-mercaptoethane sulphonate (MESNA) were tested. We found significant protective effects by several drugs used individually and also in combination with MESNA. High protection was achieved by sodium thiosulphate, which was further potentiated when combined with MESNA. Most of the selected compounds or mixture provided only moderate genoptotection without having any effect towards cell viability.